Upaya Pendidikan Akhlak di SMA Muhammadiyah Kabupaten Sambas Kalimantan Barat - Sapuadi Sapuadi; Nuraini Nuraini (El-Ghiroh : Jurnal Studi Keislaman, 2019)
This study aims to explain about moral education efforts in Sambas High School Muhammadiyah students. This research is a field research using qualitative data analysis. the results of the study that the efforts made in the formation and moral development of students in Sambas Muhammadiyah High School used two approaches. First, through a habituation approach. Habitual activities in schools such as performing the midnight prayer in congregation, carrying out reading the Qur'an, reading prayers before learning and after study, habituating to shaking hands when students meet with the teacher. Second, through the exemplary approach. Teachers who teach at Sambas Muhammadiyah High School try to be good teachers and can provide good examples of their students. This example is done to create generations that have good morals.